A new method for the characterization of microcracks based on seepage characteristics - Jiao, Guoying; Fang, Feifei; Zhang, Yuanyuan; Wu, Zhenkai; Zhang, Jie; Jiang, Zhenchang; Lv, Yingbo; Cao, Jianqi; Peng, Jinmei; He, Sijie; Wang, Yu; Guan, Qingtong (Frontiers in Earth Science, 2023)
Microcracks are the main seepage channels and reservoir space for oil and gas in dense sandstone reservoirs, and the degree of development dominates the reservoir's high and stable production capacity. A new method has been devised to address the lack of quantitative identification and characterization methods for microcracks networks. The method is based on core stress sensitivity, permeability anisotropy, and two-phase seepage rule testing. By improving upon the traditional black oil model, this method can accurately calculate the impact that microcracks of varying degrees of development have on the capacity of tight oil reservoirs. The study shows that: (1) The higher the degree of microcracks development, the stronger the reservoir stress sensitivity and the greater the permeability anisotropy. As the degree of microcracks development increases, the irreducible water saturation decreases, the residual oil saturation gradually increases, and the oil-water two-phase co-infiltration Revised manuscript with changes marked (Response to reviewers) zone becomes more extensive and smaller. The degree of microcracks development in tight reservoirs can be characterized based on the seepage characteristics parameters;(2) A microcracks characterization method and classification criteria are established.It is based on stress sensitivity coefficients, permeability anisotropy parameters, and phase seepage characteristics in cores with different microcracks development degrees.For the first time, the method enables a macroscopic-level description of microcracks seepage; (3) Numerical calculations show that the degree of microcracks development significantly affects the reservoir's oil production and water production. The higher the degree of microcracks development, the higher the reservoir's initial oil production and cumulative oil production. However, when the degree of microcracks development is too high, the microcracks are connected, thus exhibiting the nature of large fractures. This strengthens the bypassing communication effect and causes the microscopic inhomogeneity to strengthen, the oil production decreases rapidly, and water production increases quickly at the later stage. This research result enriches the reservoir microcracks characterization and evaluation system, which has essential theoretical guidance and practical significance for the rational and effective development of tight oil and tight sandstone gas.